STUDY OF SPORTS MOTIVATION OF STUDENTS FROM THE TECHNICAL UNIVERSITY OF CLUJ-NAPOCA - Mihai OLĂNESCU (Cluj University Press, 2021)
Introduction: The purpose of this article is to analyze the motivation to practice sports and physical activities among university students. Objectives: To identify the perceived reasons, as well as the existing differences between the students from the Technical University of Cluj-Napoca, regarding the motivation to practice sports and physical activities, depending on the gender and the area of residence. Methods: To find out what motivates university students to take part in various physical sports activities, we conducted a study in the academic year 2019-2020, with 257 participants. The method of quantitative research and the technique of administering questionnaires by sociological survey was used. The research tool was the Sports Motivation Scale-6 (SMS-6; Mallett et al., 2007), which is an evaluation of contextual motivation meant to ascertain the perceived reasons for practicing sports activities. Results: Regarding the behavior of practicing sports among students at the Technical University of Cluj-Napoca, male students are more motivated compared to female students and intrinsic motivation is predominant compared to other types of motivation. The area of residence does not seem to influence differently the motivation of students to practice sports, the scores obtained on each type of motivation being very close between the respondents from rural and urban areas. Conclusions: Physical education and sports are perceived by some students as a school obligation (external motivation), by others as a recreational, compensatory or recovery activity, while for most of them it means fun, a way to meet new people and to enjoy their company (intrinsic motivation). REZUMAT. Studiul motivației sportive a studenților de la Universitatea Tehnică din Cluj-Napoca. Introducere: Scopul acestui articol este de a analiza motivația de a practica sport și activități fizice în rândul studenților. Obiective: Identificarea motivelor percepute, precum și a diferențelor existente între studenții Universității Tehnice din Cluj-Napoca, cu privire la motivația de a practica sport și activități fizice, în funcție de sex și zona de reședință. Metode: Pentru a afla ce motivează studenții universitari să ia parte la diferite activități sportive, am realizat un studiu, în anul universitar 2019-2020, cu 257 de participanți. A fost utilizată metoda cercetării cantitative și tehnica de administrare a chestionarelor prin sondaj sociologic. Instrumentul de cercetare utilizat a fost Scala de motivare sportivă-6 (SMS-6; Mallett și colab., 2007), care este o măsură a motivației contextuale menită să identifice motivele percepute pentru participarea la activități sportive. Rezultate: În ceea ce privește comportamentul practicării sportului în rândul studenților de la Universitatea Tehnică din Cluj-Napoca, studenții sunt mai motivați în comparație cu studentele și motivația intrinsecă este predominantă în comparație cu celelalte tipuri de motivație. Zona de reședință nu pare să influențeze diferit motivația studenților de a practica sport, scorurile obținute pe fiecare tip de motivație fiind foarte apropiate între respondenții din mediul rural și cel urban. Concluzii: Educația fizică și sportul sunt percepute de unii studenți ca o obligație școlară (motivație externă), de alții ca o activitate recreativă, compensatorie sau de recuperare, în timp ce, pentru cei mai mulți dintre ei înseamnă distracție, un mod de a cunoaște oameni noi și de a se bucura de compania lor (motivația intrinsecă). Cuvinte-cheie: activitate fizică, motivație sport, student, universitate.